The unauthorised agent : perspectives from European and comparative law - Busch, Danny; Macgregor, Laura; Cambridge eBooks (Cambridge : Cambridge University Press, 2009)
The focus of this book, the legal situation created when an agent acts without authority, is one of the most important issues in agency law. The analysis is divided into three sections: apparent authority, ratification and the liability of the falsus procurator. Adopting a unique comparative perspective, the contributions are drawn from many different legal systems, providing the opportunity for analysis of the European common law/civil law divide. The analysis extends beyond Europe, however, taking into account the mixed legal system of South Africa, as well as the United States. Finally, there is a useful consideration of the Principles of European Contract Law and the UNIDROIT Principles of International Commercial Contracts 2004. This study will be an invaluable guide for those interested in the study of comparative law, international practitioners and those interested in the harmonisation of European Private Law.
Introduction / Danny Busch ad Laura MacGregor -- Unauthorised agency in French law / Séverine Saintier -- Unauthorised agency in Belgian law / Ilse Samoy -- Unauthorised agency in German law / Martin Schmidt-Kessel and Ana Baide -- Unauthorised agency in Dutch law / Danny Busch -- Unauthorised agency in English law / Cheng-Han Tan -- The restatement (third) of agency and the unauthorised agent in US law / Deborah A. DeMott -- Unauthorised agency, the American Restatements and other common law countries / Francis Reynolds -- Unauthorised agency in Scots law / Laura Macgregor -- Unauthorised agency in South African law / David Yuill -- Unauthorised agency in the Principles of European contract law / Danny Busch -- Unauthorised agency in the UNIDROIT principles of international commercial contracts 2004 / Danny Busch -- Comparative law evaluation / Danny Busch and Laura Macgregor -- Comparative conclusions / Danny Busch and Laura Macgregor.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Agency (Law) -- Europe; Agency (Law); Third parties (Law) -- Europe; Third parties (Law); Fraud -- Europe; Fraud; Electronic books